The Application of Carbon Nanotubes in Magnetic Fluid Hyperthermia - Grzegorz Raniszewski (Journal of Nanomaterials, 2015)
The aim of this paper is to present the results of the investigation into the applications of carbon nanotubes with ferromagnetic nanoparticles as nanoheaters for targeted thermal ablation of cancer cells. Relevant nanoparticles’ characteristics were exploited in terms of their functionality for biomedical applications and their magnetic properties were examined to determine heat generation efficiency induced by the exposure of the particles to an alternating magnetic field. The influence of the electromagnetic field on the human body tissues was assessed, providing quantitative measures of the interaction. The behavior of a liquid containing magnetic particles, during the exposure to the alternating magnetic field, was verified. As for the application for the ferromagnetic carbon nanotubes, the authors investigated temperature distribution in human liver tumor together with Arrhenius tissue damage model and the thermal dose concept.